2014
DOI: 10.1136/bmjopen-2013-004231
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, multicentre, cohort study of community rehabilitation service delivery in long-term neurological conditions

Abstract: ObjectivesPart A: To pilot the use of a register to identify and monitor patients with complex needs arising from long-term neurological conditions. Part B: To determine the extent to which patients’ needs for health and social services are met following discharge to the community after inpatient rehabilitation; to identify which factors predict unmet needs and to explore the relationship between service provision and outcomes at 12 months.DesignA multicentre, prospective, cohort study surveying participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…Indeed, observations from clinical practice indicate that HD patients in later stages tend to have a higher caregiver frequency and are more often cared for outside the home. Our findings are also in line with research on patient with long-term neurological conditions reporting that patients whose rehabilitation needs were met were more dependent at 12 months after discharge from hospital than those with unmet needs [ 33 ]. Furthermore, studies identifying unmet needs after traumatic brain injury indicate that patients with more visible needs have a higher degreee of met needs, which may reflect that health professionals are working actively and responsibly for the patient; thus, the patients are more satisfied and perceive their needs as met [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, observations from clinical practice indicate that HD patients in later stages tend to have a higher caregiver frequency and are more often cared for outside the home. Our findings are also in line with research on patient with long-term neurological conditions reporting that patients whose rehabilitation needs were met were more dependent at 12 months after discharge from hospital than those with unmet needs [ 33 ]. Furthermore, studies identifying unmet needs after traumatic brain injury indicate that patients with more visible needs have a higher degreee of met needs, which may reflect that health professionals are working actively and responsibly for the patient; thus, the patients are more satisfied and perceive their needs as met [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…A rehabilitation therapist can evaluate a patient's rehabilitation needs individually and deliver necessary interventions to the patient in the rehabilitation service. A British study reported that patients whose rehabilitation needs were unmet were more dependent and less integrated 1 year after hospital discharge than those whose rehabilitation needs were met (29). Thus, in the present study, the subsequent FIM score of stroke patients and other disease patients whose FIM change% were higher became larger when they received more community-based rehabilitation than when they received less community-based rehabilitation.…”
Section: Effectiveness Of Rehabilitation Limit To the Total Amount Osupporting
confidence: 41%
“…It does of course assume that the gains in independence are maintained. Evidence from a multicentre evaluation of community-based follow-up reported stability of dependency (and in some cases, further improvement) over the first year following discharge from the nine specialist levels 1 and 2a rehabilitation services in London, 30 suggesting that this assumption is valid—and possibly even conservative—on a population basis.…”
Section: Discussionmentioning
confidence: 99%